"Connecting the dots" – The transfer of bioscience knowledge by new graduate nurses to the clinical setting: A qualitative study. (February 2021) - Montayre, Jed; Ramjan, Lucie M.; Maneze, Della; Ho, Mu-Hsing; Maceri, Anna; Salamonson, Yenna
Abstract: Background: Little is known regarding the transfer of bioscience knowledge gained during undergraduate nursing studies into clinical practice. Objective: To explore the experiences of new registered nurses in applying bioscience concepts in their day-to-day nursing practice. Design: Descriptive qualitative design. Participants: Fifteen recently graduated registered nurses (RNs) who were working in acute care settings participated in the study. Methods: Semi-structured, face-to-face individual interviews were conducted. Interview data were audio-recorded and thematically analysed. Results: Four themes were identified from the qualitative interviews. The first and second themes demonstrated nurses' realisation of the relevance of theoretical bioscience knowledge learnt within the classroom to their practice and how this evidence-based knowledge translated into confidence in decisions made. The third and fourth themes revealed the impact bioscience knowledge had on RNs' relationships with patients and family members, which was viewed as providing compassionate care. Conclusions: The application of knowledge in biosciences gained during their undergraduate years, provided the basis for RNs to trust in their own clinical judgment and to speak with conviction. 'Connecting the dots' between bioscience knowledge and clinical practice provided the platform for RNs to gain and build trust with their patients. The practical utility of bioscience knowledge in everyday practice allowed RNs to contextualise their nursing care regimen and tailor holistic nursing care delivery to individual patient needs.